Biomechanical grounds for fixing an endoprosthesis of the temporomandibular joint to the mandible - Liubchenko, Alexandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with biomechanical grounds for using a new Ukrainian total endoprosthesis of the temporomandibular joint in bilateral ankylosis of the temporomandibular joints. With help of the finite-element method, a stress-deformed state of the bone tissue was studied in the region, where the mandibular part of the endoprosthesis was fixed. It was proved that though the above stress significantly increased, its value did not exceed any permissible bone tissue stresses.